Kebijakan Formulatif Tindak Pidana Perdagangan Orang (Trafficking) - Nanda Ivan Natsir (Fakultas Hukum Universitas Mataram, 2016)
Crime of human trafficking (human trafficking) is a violation of human rights as a form of slavery. To encourage the Indonesian government to protect through legal arrangements with the issuance of Law No. 21 of 2007 on the Eradication of Trafficking in Persons. The focus of the issues raised in this research is how the forms of the crime of trafficking in persons under Law No. 21 of 2007, and how the criminal law policy in combating the crime of human trafficking. The results showed that the forms of the crime of trafficking in persons under Law No. 21 of 2007, namely: First, the recruitment process sexual exploitation (prostitution). Second, trafficking of children as workers, Third, child trafficking through adoption (adoption). Fourth, the policy of criminal law in combating the crime of trafficking in persons (human trafficking) are listed in the Criminal Code, RKUHP 2015, Law No. 39 of 1999 on Human Rights, Law No. 23 of 2002 on Child Protection and Law No. 21 2007 About the Crime of Trafficking in Persons which contains all provisions concerning human trafficking